Pengolahan Lindi (Leachate) dengan Metode Koagulasi – Flokulasi dan Sedimentasi Menggunakan Koagulan Aluminium Sulfate (Al2SO4) dan Poly Alumunium Chloride (PAC) - Nia Oktaverina; Atik Widianti (Prosiding Seminar Teknologi Kebumian dan Kelautan (SEMITAN), 2021)
One of the TPSTs in Sidoarjo Regency is a place that is designated for the collection, sorting, reuse, recycling, processing and final processing of waste. These activities cause environmental problems that come from waste water called leachate. So that it is necessary to have a process that can reduce the contaminant content in leachate. This study aims to treat leachate from one of the TPSTs in Sidoarjo Regency with the coagulation - flocculation and sedimentation method using Aluminum Sulfate (Al2SO4) and Poly Aluminum Chloride (PAC) coagulants.  The coagulation - flocculation and sedimentation process uses a 1: 3 dilution with a value of one for leachate and a value of three for air. The stirring speed of the coagulation was 120 rpm for 10 minutes, the flocculation was 45 rpm for 20 minutes and the sedimentation process was 24 hours. From the results of parameter measurement for each coagulant variation, it can be concluded that the Al2SO4 coagulant with a dose of 16 g / L is added to the leachate sample, the smaller the pH, TDS, TSS, BOD5 and COD values of the leachate. Whereas the addition of PAC coagulant at a dose of 30 g / L, the smaller the NH4-N value in leachate